A Study of the Brönsted Site Acidity of Crystalline and Amorphous Aluminosilicates: 1. Desorption of Ammonia, Dehydration of 2-Propanol and Cracking of Cumene - V.V. Brei; V.A. Kaspersky; K.N. Khomenko; A.A. Chuiko (Adsorption Science & Technology)
The acidity of the H-form aluminosilicates, which include ZSM-5, mordenite, Y-faujasite, Al-containing aerosils and silica gels, and the layering of aluminosilicate compounds on an aerosil surface was measured by temperature-programmed mass spectrometry desorption (TPD) of NH 3 . It was found that the desorption energies of NH 3 decrease in the order: H-M > H-ZSM-5 > Al-aerosils> H-Y > CVD Al-silicates> Al-silica gels. The catalytic activities of the studied samples in 2-propanol dehydration and cumene cracking have been shown to decrease in the same order.